ANALYSIS OF PHONEME BETWEEN RANTAU PANDAN DIALECT AND RANTAU DUKU DIALECT - vera magria (Krinok:Jurnal Linguistik Budaya, 2017)
This research aims to identify the similarities and differences between phoneme of Rantau Pandan and Rantau Duku dialect. The data collection was done by using observation technique. Furthermore, the writer applied basic technique, continuing technique, record technique and writing technique. In gaining the data, the writer uses 200 words taken from Swadesh basic vocabularies, part of bodies, verb,noun and word orderThe result of this study indicates that there are similarities and differences of phoneme between Rantau Pandan dialect and Rantau Duku dialect. Out of 200 words, 120 are pronounced similarly in both dialects. The similarities may occur because both dialects have one root, i.e. Rantau Pandan Language.Meanwhile, there are 80 words which are uttered differently in both dialects. The differences are happened in phonemic change and phonemic deletion. The phonemic changes include the alteration of vowel and consonant sounds. In Meanwhile, the phonemic deletion includes the omission of vowel, consonant, and syllable.Key Words:      Phonemes, Rantau Pandan, Rantau Duku, Dialect